Who empowers women towards healthier lifestyles? : example from western Croatia - Vitale, Ksenija (Array, 2009)
Summary: This article explores who among the doctors, other health care workers, family or somebody else most frequently advised women about their lifestyle changes related to cardiovascular health (including smoking, nutritional habits and physical activity). Sample was a part of comprehensive Croatian Adult Health Survey, comprised of women from Primorje-Goran, Istra and Lika-Senj Counties. Results indicated low frequency of advising on lifestyle changes in primary health care in all three counties, with most advice from general practitioners on nutritional habits.